2001
DOI: 10.1038/sj.leu.2402181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of recombinant adenovirus-mediated expression of wild-type p53 and p27Kip1 on cell cycle and apoptosis in SUDHL-1 cells derived from anaplastic large cell lymphoma

Abstract: Recombinant adenoviruses expressing wild-type p53 (AdWTp53) and p27 Kip1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…[17][18][19] For the first time, we showed that adenovirus-mediated p27 Kip1 expression was able to induce in vitro apoptosis in SUDHL-1 cells derived from t(2:5)-ALCL. 20, 21 We also demonstrated that the effects of adenovirus-mediated p27 Kip1 expression were cell dependent and differed from the effects of adenovirus-mediated p53 expression in SUDHL-1 cells. 20 22 On the contrary, cells derived from HD were resistant to apoptosis induced by the same recombinant adenoviruses.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 70%
See 4 more Smart Citations
“…[17][18][19] For the first time, we showed that adenovirus-mediated p27 Kip1 expression was able to induce in vitro apoptosis in SUDHL-1 cells derived from t(2:5)-ALCL. 20, 21 We also demonstrated that the effects of adenovirus-mediated p27 Kip1 expression were cell dependent and differed from the effects of adenovirus-mediated p53 expression in SUDHL-1 cells. 20 22 On the contrary, cells derived from HD were resistant to apoptosis induced by the same recombinant adenoviruses.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 70%
“…In fact, other investigators and we have recently elucidated this concept in studies that will be discussed. 12,15,[20][21][22] In one study, we showed that the recombinant adenovirusmediated expression of exogenous p27 Kip1 was equally efficient in the cytoplasm and in the nucleus of SUDHL-1 and KARPAS 299 cells derived from t(2;5)-ALCL. 20 The presence of CAR and integrins on the cell surface of SUDHL-1 (Ref.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 99%
See 3 more Smart Citations